1990
DOI: 10.2514/3.194
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer across aluminum/stainless-steel surfaces in periodic contact

Abstract: form a wake. This is further support of the Kelvin-Helmholtz mechanism of vapor film instability.Liquid-solid contact data reported by Chang 3 showed that for the velocities in our experiments the liquid-vapor interface separating the liquid wake from the vapor wake probably experiences a Taylor-like instability. That is, the liquid above the vapor wake can fall through the interface and touch the heater surface. Thus film boiling heat transfer analyses for upflowing liquids over cylinders should include this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…(4) with a constant heat flux boundary condition atjc = L dT (7) a solution can be obtained which, when incorporated into Duhamel's method, 9 can be used to solve Eqs. (2)(3)(4)(5).…”
Section: Solution Methodsmentioning
confidence: 98%
“…(4) with a constant heat flux boundary condition atjc = L dT (7) a solution can be obtained which, when incorporated into Duhamel's method, 9 can be used to solve Eqs. (2)(3)(4)(5).…”
Section: Solution Methodsmentioning
confidence: 98%
“…Moses and Johnson [14] also experimentally examined the approach to the quasi-steady-state condition for similar metallic surfaces in periodic contact, focusing on the behaviour of the TCC during the contact portion of a cycle and on the number of cycles required to reach a quasi-steady state condition. Dodd and Moses [15] extended this set of experiments to consider periodic contacts between aluminium and stainless steel. Results for this single case of periodic contact between dissimilar metals indicated that the same transient behaviour of the TCC was observed for all metal pairs.…”
Section: Introductionmentioning
confidence: 98%
“…However, for dissimilar contact materials, the influence of the material with a lesser thermal conductivity was prevailing. Other studies relating to the TCC between flat surfaces could be found in References [19,20,[22][23][24][25][26][27]. Kumar and Tariq 11,28 investigated the timedependent interfacial heat transfer/TCC between steel-steel conforming (surface) as well as nonconforming (line) contacts under various loadings.…”
Section: Introductionmentioning
confidence: 99%